Association of health literacy with obesity and overweight among arabic secondary school students in Kuala Lumpur and Putrajaya, Malaysia - R., Eltayeb; M. S., Salmiah; I., Suriani (Community Health Society Malaysia (CHSM), 2016)
Background: Overweight and obesity among adolescents is considered an epidemic in both developed and developing countries. There is still limited study on the health literacy as a determinant of overweight and obesity in adolescents.The aims of this study was to determine the association of health literacy with overweight and obesity.